1996
DOI: 10.1021/jf950814c
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Composition of Cilantro

Abstract: Leaf oil was isolated from two commercial samples of cilantro (Coriandrum sativum L.) and from growth-chamber-grown plants at five different stages of growth. The oils were analyzed by GC/MS. They were found to be composed mainly of C10−C16 aldehydes. (E)-2-Alkenals predominated. Substantial quantitative differences were observed between the two cilantro samples and in the leaf oils isolated at different growth stages. The data indicate that cilantro oil may exhibit significant variation in composition due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 3 publications
4
45
1
Order By: Relevance
“…The total percentage of OM in this respect recorded (66.72%) against 8.6, 2.86, 0.7 and 5.9% for (MH), (SH), (OS) and (VC) group, respectively. Similar results have been reported by many investigators [7,8,10,17], which showed that the main compound in coriander seed essential oil was linalool. Among the other constituents of coriander seed oil identified in this work are, α-pinene (2.28%) and -caryophyllene (2.51%).…”
Section: Coriander (C Sativum) Herb Oilsupporting
confidence: 91%
See 2 more Smart Citations
“…The total percentage of OM in this respect recorded (66.72%) against 8.6, 2.86, 0.7 and 5.9% for (MH), (SH), (OS) and (VC) group, respectively. Similar results have been reported by many investigators [7,8,10,17], which showed that the main compound in coriander seed essential oil was linalool. Among the other constituents of coriander seed oil identified in this work are, α-pinene (2.28%) and -caryophyllene (2.51%).…”
Section: Coriander (C Sativum) Herb Oilsupporting
confidence: 91%
“…E. Ibrahim melsayed49@yahoo.com fruit (mature) with a yield of 0.14%, 0.23%, 0.37% and 0.31% (w/w), respectively [8]. The chemical class characters of coriander essential oils from different fruit samples have been represented by Sriti et al [7]: Seeds of C. sativum yielded 0.8%, yellow oil, with a pleasing aroma, containing oxygenated monoterpenes (80.47%), monoterpene hydrocarbon (6.45%) [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fresh green leaves, commonly known as cilantro or Chinese parsley (Potter 1996), are widely featured in the cuisines of China, Mexico, South America, India and Southeast Asia. They possess unique aroma and also are widely used as food flavoring or to mask unpleasant odors of certain foods (Potter 1996;Gil et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The aromatic components and the volatile compounds of the spice oil have also been reported as having bactericidal effect against microorganisms such as Salmonella choleraesuis (Kubo et al, 2004). Although coriander is an important food material as an herb, limited investigations into its changes of odor according to growth period and differences among its organs, have been conducted (Potter, 1996).…”
Section: Introductionmentioning
confidence: 99%